A SIMPLE METHOD OF IN-VITRO CULTURE OF PLASMODIUM FALCIPARUM IN SCREW-CAPPED VIALS1 - H.Edrissian Pharm; A.Afshar (Tehran University of Medical Sciences, 1982)
In a preliminary study carried out in a simple field laboratory in Bandar-Abbas, southern Iran, five isolates of P. falciparum collected from the patients was cultured in RPMI 1640 medium with human serum in the tightly closed screw capped vials without any devised system for adjustment of co2 and o2 mixture. The same isolates were also cultured, simultaneously, in Petri-dishes using Jensen-Trager candle, jar method. Although, the cultures could not be maintained more than 27 days, mostly due to unfavorable conditions existed in the laboratory, the longevity of parasites were more or less the same in both techniques. In this study the multiplication rates of parasites in the screw capped vials were higher than rates obtained in Petri dishes in candle jar method.